Analysis of the efficiency of intensity measures from real earthquake data recorded in buildings. Issue 147 (August 2021) - Ghimire, Subash; Guéguen, Philippe; Astorga, Ariana
Abstract: In this paper, a number of spectral and ordinary ground motion intensity measures (IMs) are tested for use in structural performance assessment. Real strong motion values recorded at the top and the bottom of US, Japanese and Romanian buildings are analyzed in order to identify the source of uncertainties in the prediction of engineering demand parameters (i.e. structural drift) for given IMs (i.e. σEDP|IM ). The efficiency and sufficiency of each IM from a large set of building and earthquake motion data are tested for different criteria characterizing the seismic source (magnitude and source-to-site distance), and considering several building classes and a specific single-building analysis including aging due to cumulative earthquake damage over time. The spectral values at co-seismic resonance frequencies was found to be the most efficient IMs for the range of buildings and earthquakes investigated, particularly for velocity with a reduction of approximately 50% of the σEDP|IM value. Conversely, most IMs are relatively insufficient. Highlights: Integrating real structural state lowers building response prediction uncertainties. The spectral values at co-seismic resonance frequencies are the most efficient IMs. Building frequency change during earthquakes. A simple empirical building damage prediction equation is developed.